PEMANFAATAN NILAI-NILAI DALAM LEGENDA POPULER AMAT RHANG MANYANG SEBAGAI ASET WISATA BUDAYA DI KABUPATEN ACEH BESAR - Arfan, Fahmi; Azmi, Nurul; Asriani, Asriani; Mahyidin, Razali; Yulizar, Meri (Jurnal Dedikasi Pendidikan, 2025)
The utilization of values in the popular legend of Amat Rhang Manyang is considered as one of the biggest factors in attracting tourists. This is because folk legends can shape children's personalities because they contain life values. Strengthening these values is important to instill in order to influence their lives. The legend of Amat Rhang Manyang was chosen because it has values that are useful to be applied in everyday life. This study aims to describe the legendary values contained in the legend of Amat Rhang Manyang as a cultural tourism asset in Aceh Besar Regency. The source of research data is the legend of Amat Rhang Manyang. The research method used is descriptive qualitative with data collection techniques in the form of observation and interviews with sources. Based on the results of the research and discussion, the values contained in the legend of Amat Rhang Manyang are religious values, moral values, cultural values and social values. After going to the field, it showed that the lack of tourism promotion activities for the legend of Amat Rhang Manyang resulted in low tourist visits. In fact, if managed properly, the legend area of Amat Rhang Manyang can contribute to increasing regional income or income, opening up new jobs and can help alleviate poverty in the area around the legend area